Development of Webador Based Learning Media for Basic Vocational Education Courses among Tenth Grade Office Management Students - Rinike Neila Pitaloka; Dedi Purwana E.S; Susan Febriantina (The Future of Education Journal, 2026)
This study was motivated by the predominance of conventional teaching methods, which resulted in low student engagement and learning motivation, as well as the lack of integrated digital learning media that support learning needs in the digital era. This study aimed to develop Webador-based learning media for the Basic Office Management and Business Services subject in Grade X Office Management, determine the feasibility of the developed media, and examine its practicality based on students’ responses. This study employed the Research and Development (R&D) method using the 4-D development model (Define, Design, Develop, and Disseminate). The research subjects consisted of Grade X Office Management students at SMKN 16 Jakarta. Data collection techniques included expert validation sheets and student response questionnaires, which were analyzed using quantitative and qualitative descriptive analysis. The results showed that the Webador-based learning media obtained a material expert validation score of 95% and a media expert validation score of 91%, both categorized as highly feasible. The practicality test results showed a score of 96% in the small-group trial and 99% in the large-group trial, both categorized as highly practical. Therefore, the Webador-based learning media was declared feasible and practical to be used as an alternative digital learning medium in the Basic Office Management and Business Services subject for Grade X Office Management students.